Chemical and paf activity of several Malaysian artocarpus - M. Sirat, Hasnah; Jamil, Shajarahtunnur (Universiti Teknologi Malaysia, 2005)
Phytochemical studies of Artocarpus lowii King,A. scortechinii King and A. teysmanii Miq. have resulted in the isolation of four new compounds and eight known compounds. Three new compounds have been successfully isolated from A. lowii King, i.e 2 ' ,4 ' -dihydroxy-4-methoxy-3 ' -prenyldihydrochalcone, 2 ' ,3,4 ' ,4-tetrahydroxy-3 ' - prenylchalcone and 2-hydroxyparatocarpin C. Three known compounds were identified as cycloheterophyllin, 2 ' ,4 ' ,4-trihydroxy-3 ' -prenylchalcone and 4-hydroxylonchocarpin. A new compound was isolated from A. scortechinii King and was identified as 2 ' ,4 ' ,5 ' ,5- tetrahydroxy-3-geranyl-7,8-(2,2-dimethyl-6 H -pyrano)-6-prenylflavone together with three known compounds, i.e arto nin E, artobiloxanthone and lupeol 3-acetate. Four known compounds were isolated from A. teysmanii Miq., which were identified as artonin E, artobiloxanthone, artonol B and cycloartobiloxanthone. The structures of all compounds were established based on spectral studies using nuclear magnetic resonance spectroscopy, mass spectrometry, infrared spec troscopy and ultraviolet spectroscopy. The biological studies on the crude extracts and pure compounds of these three species showed that several pure compounds have signi ficant biological activit y especially in the platelet aggregation assays. Cycloheterophy llin, artonin E, isobavachalcone and 2 ' ,4 ' - dihydroxy-4-methoxy-3 ' -prenyldihydrochalcone totally inhibited ADP-induced platelet aggregation compared to standard aspirin which suppressed only 31.6% of the platelet aggregation